Analisis Pengaruh Modal Dan Upah Tenaga Kerja Terhadap Pendapatan Usaha Kecil Menengah Kerajinan Kayu Di Dusun Rejoso Kecamatan Junrejo Kota Batu - Novita Wulandari (Jurnal Ilmu Ekonomi, 2021)
This study aims to analyze the effect of capital and labor wages on income. The data used are 25 respondents of wood craftsmen in Rejoso Hamlet, Junrejo District, Batu City. The method used in this research is multiple linear regression and hypothesis testing. The study results indicate that the variables of capital and labor wages have a positive and significant effect on the income of small and medium woodcraft businesses in Rejoso Hamlet, Junrejo District, Batu City. It can be suggested that the craftsmen are expected to be able to increase the capital they have to get a higher income because money is one of the main aspects that affect revenue